2006
DOI: 10.1038/sj.bjc.6603449
|View full text |Cite
|
Sign up to set email alerts
|

Molecular subtypes of breast cancer and amplification of topoisomerase IIα: predictive role in dose intensive adjuvant chemotherapy

Abstract: Benefit from chemotherapy treatment in breast cancer patients is determined by the molecular make-up of the tumour. In a retrospective analysis, we determined the molecular subtypes of breast cancer originally defined by expression microarrays by immunohistochemistry in tumours of patients who took part in a randomised study of adjuvant high-dose chemotherapy in breast cancer. In addition, the topoisomerase IIa (TOP2A) amplification status was determined by fluorescence in situ hybridisation and chromogenic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 25 publications
6
50
0
1
Order By: Relevance
“…TNBC is a more invasive cancer with higher degree of recurrence. About 14 to 20 percentages of breast cancers are triple negative (Carey et al, 2006;Hannemann et al, 2006;Lund et al, 2010). Similar to our study, the significant increase of the triple negative tumors with decrease of cancer onset age has been shown in many other studies in different countries that TNBC has been more frequent in younger ages (Dobi et al, 2011;Salami et al, 2011).…”
Section: Discussionsupporting
confidence: 79%
“…TNBC is a more invasive cancer with higher degree of recurrence. About 14 to 20 percentages of breast cancers are triple negative (Carey et al, 2006;Hannemann et al, 2006;Lund et al, 2010). Similar to our study, the significant increase of the triple negative tumors with decrease of cancer onset age has been shown in many other studies in different countries that TNBC has been more frequent in younger ages (Dobi et al, 2011;Salami et al, 2011).…”
Section: Discussionsupporting
confidence: 79%
“…This has been confirmed in various ethnic populations [25][26][27][28][29][30]. Therefore, they can be used to estimate the prevalence of the five intrinsic subtypes in epidemiological studies without loss of their prognostic significance [22,25,31]. IHC of receptors for female steroid hormones and HER-2 remains the most common practice in the primary evaluation of breast cancer.…”
Section: Introductionmentioning
confidence: 87%
“…[41][42][43] Because of this coincidence, many researchers have hypothesized that TOP2A amplification might become the gold standard predictive factor for anthracyclines, rather than ERBB2; and many retrospective studies have been conducted to assess its predictive value. However, although several studies 19,39,42,44 have shown that TOP2A alterations are associated with an increased responsiveness to anthracycline-containing regimens, others 20,45 have been inconclusive.…”
Section: Top2a In Breast Cancer 1457mentioning
confidence: 99%